On Boundaries Finding the Essence of the Right to the Protection of Personal Data - Porcedda, Maria (Hart Publishing, 2018)
In this contribution, I identify the essence of the right to the protection of personal data as understood in EU law. The essence is a fundamental step in defining the permissible limitations of the right; it works as a theoretical border, the trespassing of which leads to the automatic violation of the right. I claim that, in order to find the essence, it is first of all necessary to trace the contours of the right to the protection of personal data. In its case law on the protection of personal, the CJEU has hitherto followed a susbstantive approach to the essence of Article 8 of the Charter withouth, however, providing indications on how it reached its conclusions. I therefore supplement the scant case law of the CJEU with work on indicators developed by the OHCHR, which provides a method for identifying attributes of rights from which I distil the essence. While the final definition of the essence largely depends on the findings of the CJEU, nevertheless this does not imply that discussing the essence is taboo. This is because defining, even if temporarily, the content of the essence and related attributes has relevance beyond the courtroom. The proposed attributes and essence can help in gaining granularity when analysing the intrusiveness of technologies on the right to the protection of personal data (and other rights), and support data protection by design approaches.
Data Protection and Privacy. The Internet of Bodies
PUBLISHED
Keywords: Digital Humanities; Identities in Transformation; Telecommunications; Data Protection Law; European law; Governance, Human Rights, European Union Law; IT law